Ability of Lactobacillus kefiri LKF01 (DSM32079) to colonize the intestinal environment and modify the gut microbiota composition of healthy individuals. Issue 3 (March 2017) - Toscano, Marco; De Grandi, Roberta; Miniello, Vito Leonardo; Mattina, Roberto; Drago, Lorenzo
Abstract: Background: Probiotics have been observed to positively influence the host's health, but to date few data about the ability of probiotics to modify the gut microbiota composition exist. Aims: To evaluate the ability of Lactobacillus kefiri LKF01 DSM32079 (LKEF) to colonize the intestinal environment of healthy subjects and modify the gut microbiota composition. Methods: Twenty Italian healthy volunteers were randomized in pre-prandial and post-prandial groups. Changes in the gut microbiota composition were detected by using a Next Generation Sequencing technology (Ion Torrent Personal Genome Machine). Results: L. kefiri was recovered in the feces of all volunteers after one month of probiotic administration, while it was detected only in three subjects belonging to the pre-prandial group and in two subjects belonging to the post-prandial group one month after the end of probiotic consumption. After one month of probiotic oral intake we observed a reduction of Bilophila, Butyricicomonas, Flavonifractor, Oscillibacter and Prevotella . Interestingly, after the end of probiotic administration Bacteroides, Barnesiella, Butyricicomonas, Clostridium, Haemophilus, Oscillibacter, Salmonella, Streptococcus, Subdoligranolum, and Veillonella were significantly reduced if compared to baseline samples. Conclusion: L. kefiri LKF01 showed a strong ability to modulate the gut microbiota composition, leading to a significant reduction of several bacterial genera directly involved in the onset of pro-inflammatory response and gastrointestinal diseases.